3-bar tensegrity units with non-equilateral triangle on an end plane. (September 2018) - Liu, Heping; Zhang, Jingyao; Ohsaki, Makoto
Highlights: New 3-bar tensegrity units with non-equilateral triangle on an end plane are presented. Analytical solutions for self-equilibrium analysis are derived. Geometrical parameters and force densities of self-equilibrium configurations are analyzed. Abstract: The well-known 3-bar prismatic tensegrity unit has equilateral triangles on the two end planes. In this paper, properties of the 3-bar tensegrity unit with non-equilateral triangle on one end plane are investigated. The unit is generated by transforming the equilateral triangle of the tensegrity prism to a triangle with irregular shape. The self-equilibrium equations of the 3-bar tensegrity unit are analytically solved for geometrical parameters and force densities of the members. The analytical solutions are utilized to investigate detailed characteristics of the 3-bar tensegrity units with non-equilateral triangle on an end plane. Graphical abstract: Image, graphical abstract